Chief probation officers : a criminal justice elite, 2000-2002 - Mair, George (UK Data Service, 2004)
The project aimed to carry out the first detailed empirical study of Chief Probation Officers (CPOs) in England and Wales. The objectives of the study were: to investigate the social and educational backgrounds and career histories of CPOs; to explore their perceptions of community penalties, developments in these over the course of their careers and potential changes in the future; to examine the role of CPOs as managers and their relationships with central government, local agencies and their probation committees. The study consisted of 47 qualitative interviews with CPOs, lasting on average around two hours each.